Real Time Thermal Imaging of Solid Oxide Fuel Cell - Jasiński, M.; Ziewiec, K.; Wojciechowska, M. (Archives of Metallurgy and Materials, 2019)
In this work, a mid infrared thermography was used to study thermal behavior of solid oxide fuel cell (SOFC) with a circular shape and a diameter of 90 mm. The emissivity of the anodic surface of the fuel cell was determined to be from 0.95 to 0.46 in the temperature range 550-1200 K and the profile and temperature distribution of the anodic surface of the unloaded cell was given. The surface temperature of the cell was determined during operation and the polarity changes from open circuit voltage (OCV) to 0.0 V. It was found that the cell self-heating effect decreases with increasing temperature of the cell.
Keywords: thermography; solid oxide fuel cell; sofc; thermal imaging; infrared